STATUS OF POLYCYCLIC AROMATIC HYDROCARBON CONTAMINATION IN PALLIKARANAI WETLAND: FISH AS AN INDICATOR: Life Science-Toxicology - DEVARAJAN, MYTHREYI; MURALIDHARAN, SUBRAMANIAN; NAMBIRAJAN, KANTHAN; PRAKASHAM, KARTHIKEYAN (International Journal of Life Science and Pharma Research, 2019)
Pallikaranai Wetland, within Tamil Nadu, India, receives runoff from the surrounding urban area, including polycyclic aromatic hydrocarbons (PAHs). PAH have been listed as Priority Pollutants by US EPA (2014) due to their carcinogenic, genotoxic and teratogenic potential in humans and form DNA adducts. In addition to the run-off that the area receives, dumping and burning of waste occurs here and hence, this study was designed to evaluate PAH contamination in three fish species commonly found in the wetland considering the ongoing indiscriminate dumping of assorted waste here. Between January and April 2018, fifty fish comprising of seven subjects of Oreochromis aureus, thirty four subjects of Oreochromis mossambicus and nine subjects of Oreochromis niloticus were collected from Pallikaranai wetland. The fish were then necropsied and were analysed for fifteen PAH. Total PAH load was greatest in Oreochromis mossambicus. Naphthalene and phenanthrene were detected in all samples. While levels of sum of four carcinogenic (PAH4: Sum of Benzo (a) pyrene, Chrysene, Benzo (a) anthracene and Benzo (b) fluoranthene) in one subject of Oreochromismossambicus manifolds higher than the toxic levels as per the European Union guidelines, and was closely trailing the limits in one individual of Oreochromisaureus, the levels of the other 48 fish were below the limit of concern. Oreochrmoismossambicus is near threatened in its home range (Mozzambique) according to the IUCN and PAH may be contributing to the threats that the species faces. While the Oreochromis mossambicus is not threatened in India, it is imperative to assess the accumulation patterns of PAH in the species elsewhere to contribute data to the conservation in the home range.